Anxiety and speaking in people who stutter: An investigation using the emotional Stroop task - Hennessey, Neville; Dourado, E.; Beilby, Janet (Elsevier, 2014)
People with anxiety disorders show an attentional bias towards threat or negative emotion words. This exploratory study examined whether people who stutter (PWS), who can be anxious when speaking, show similar bias and whether reactions to threat words also influence speech motor planning and execution. Comparisons were made between 31 PWS and 31 fluent controls in a modified emotional Stroop task where, depending on a visual cue, participants named the colour of threat and neutral words at either a normal or fast articulation rate. In a manual version of the same task participants pressed the corresponding colour button with either a long or short duration. PWS but not controls were slower to respond to threat words than neutral words, however, this emotionality effect was only evident for verbal responding. Emotionality did not interact with speech rate, but the size of the emotionality effect among PWS did correlate with frequency of stuttering. Results suggest PWS show an attentional bias to threat words similar to that found in people with anxiety disorder. In addition, this bias appears to be contingent on engaging the speech pro-duction system as a response modality. No evidence was found to indicate that emotional reactivity during the Stroop task constrains or destabilises, perhaps via arousal mechanisms, speech motor adjustment or execution for PWS.